2011
DOI: 10.1186/1476-072x-10-51
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the spatially varying relation between cervical cancer and socio-economic conditions in England

Abstract: BackgroundGeographically weighted Poisson regression (GWPR) was applied to the relation between cervical cancer disease incidence rates in England and socio-economic deprivation, social status and family structure covariates. Local parameters were estimated which describe the spatial variation in the relations between incidence and socio-economic covariates.ResultsA global (stationary) regression model revealed a significant correlation between cervical cancer incidence rates and social status. However, a loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Indeed, a socioeconomic factor may be more relevant as determinant of stroke in some municipalities (or group of municipalities) and less in others. Local Poisson GWR results successfully revealed the existence of spatial patterns in the spatially varying coefficients in this study, as already observed in other studies following this methodology for other diseases (St-Hilaire et al, 2010;Cheng et al, 2011;Helbich et al, 2012;Weisent et al, 2012). This pattern was also apparent in a very recent communication focusing on geographic disparities with respect to neighbourhood for heart attack and stroke in Tennessee, USA (Odoi and Busingye, 2014).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Indeed, a socioeconomic factor may be more relevant as determinant of stroke in some municipalities (or group of municipalities) and less in others. Local Poisson GWR results successfully revealed the existence of spatial patterns in the spatially varying coefficients in this study, as already observed in other studies following this methodology for other diseases (St-Hilaire et al, 2010;Cheng et al, 2011;Helbich et al, 2012;Weisent et al, 2012). This pattern was also apparent in a very recent communication focusing on geographic disparities with respect to neighbourhood for heart attack and stroke in Tennessee, USA (Odoi and Busingye, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Since it estimates regression coefficients for each location in the study area, maps generated from these data play an important role in exploring and interpreting spatial nonstationarity (Mennis, 2006). With this in mind, several studies have already implemented this method, aiming to improve our understanding of the determinants of geographic disparities of Health (St-Hilaire et al, 2010;Cheng et al, 2011;Helbich et al, 2012;Weisent et al, 2012). There is some controversy surrounding GWR, with some authors stating that this technique is more suitable for exploratory analysis.…”
Section: Spatial Variability Of Associations Between Stroke and Its Dmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fixed kernel, the optimal distance away from the regression point will be found; for adaptive, the optimal number of neighbors for use in the regression will be found. To avoid large standard errors and bias in local parameter estimates (due to either few data points in a short distance or a large number of points with a long distance to the regression point i) an optimal size of bandwidth is necessary (Cheng et al 2011). In this study, the Akaike Information Criterion with a correction for finite sample sizes (AICc) (Fotheringham et al 2002) was used as indicator to analyze the performance or goodness of fit of the models and the performance of the bandwidth, where the model with the minimum AICc value was selected as having the optimum bandwidth.…”
Section: Global Poisson Regression (Gpr) and Geographically Weighted mentioning
confidence: 99%
“…Where Se refers to the local standard error of the kth parameter estimate, taking in account the variation in the data (Cheng et al 2011). Pseudo t-values follow approximately a standard normal distribution if the true regression parameter is zero and mapping them is useful for identifying spatial variations in relationships between explanatory covariates and the outcome covariate.…”
Section: Global Poisson Regression (Gpr) and Geographically Weighted mentioning
confidence: 99%